Adaptive architecture : changing parameters and practice - Preiser, Wolfgang F. E.; Hardy, Andrea; Wilhelm, Jacob J. (New York : Routledge, Taylor & Francis Group, 2018)
"The constant in architecture's evolution is change. Adaptive Architecture explores structures, or environments that accommodate multiple functions at the same time, sequentially, or at periodically recurring events. It demonstrates how changing technological, economic, ecological and social conditions have altered the playing field for architecture from the design of single purpose structures to the design of interacting systems of synergistically interdependent, distributed buildings. Including contributors from the US, UK, Japan, Australia, Germany and South Africa, the essays are woven into a five-part framework which provides a broad and unique treatment of this important and timely issue."
Part I. Introduction / Wolfgang F.E. Preiser, Thomas Fisher, Andrea Hardy --
Part II. Concepts and processes for future flexibility : Preamble / Allison Lenell Magley --
Challenges of large-scale housing in the developing world: the Habitat for Humanity Global Village project in Ethiopia / Allison Lenell Magley --
Predesign planning for flexibility / Robert G. Hershberger, Molly E. Smith --
Multi-performance spaces: assessing the impacts of an innovative LEED (TM) platinum educational complex on the triple bottom line / Ihab M.K. Elzeyadi --
Mixed-use development using air rights above the JR train station at Nagoya, Japan / Gen Taniguchi, Akikazu Kato, Shiho Mori --
Prospects for adaptive, inclusive design: lessons learned from children's museums / Korydon Smith and Beth Tauke --
Reflections on Part II / Michael J. Crosbie --
Part III. Rooms/settings scale : Preamble : William Fawcett --
The measurement and efficiency of adaptive design strategies / William Fawcett --
Finding the balance: a model of assessment for commercial floor-plate performance / Jeffrey L. Morgan --
Beyond the cellular office: adaptable offices for medium-sized companies / Martin Hodulak --
Adaptive architecture of the London Science Museum: a needs assessment / Kristin E. Hibbs --
Post-occupancy evaluation of a multi-tasking environment: the University of Kentucky Medical Center's emergency department / Lindsey L. Fay --
A construct of generosity in Navajo culture: the Hogan / Jaclyn M. Roessel --
Reflections on Part III / Michael J. Crosbie --
Part IV. Building scale : Preamble / Wolfgang F.E. Preiser, Jacob J. Wilhelm --
Keren Or Center for Blind Children with Multiple Disabilities in Israel / Wolfgang F.E. Preiser, Jacob J. Wilhelm --
Omgivning: transforming historic icons through adaptive reuse / Karin Liljegren, Kelly Kish --
Strategies for planning, designing, and operating adaptable facilities / John P. Petronis, Faye Whittemore, and Andy L. Aguilar --
Native meets high-tech: the Sobeloff Center, Sealaska Heritage Corporation / Zane M. Jones --
Building with boxes: the New Jerusalem Children's Home / Mia L.C. Anfield --
Reflections on Part IV / Michael J. Crosbie --
Part V. Urban scale : Preamble / Andrea E. Hardy --
Reappropriation of city infrastructure: alleyways / Andrea E. Hardy --
Concourse to campus: transforming Berlin TXL Airport into a higher education space / Una Rath, Martin Hodulak --
An adaptive evolution from Prussian artillery barracks to intelligent campus buildings / Ulrich Schramm --
A case study on the design of the Scottish Crime Campus / Gordon Murray --
Multi-tasking architectural computer programs: BIM / Akikazu Kato, Shiho Mori, Gen Taniguchi --
Reflections on Part V / Michael J. Crosbie --
Part VI. Epilogue : The International Space Station: adaptive human accommodations in an extreme, isolated environment / David Fitts, Jennifer L. Rochlis, Mihriban Whitmore, Alexandra Whitmore --
Appendix : The habitability paradigm: key elements and concepts for a humane architecture / Wolfgang F.E. Preiser, Andrea E. Hardy, Jacob J. Wilhelm.
Includes bibliographical references and index.
ARC
Trim Education
Keywords: Architectural design; Buildings -- Performance; Architecture and society; Architecture